Behavioral architecture of opioid reward and aversion in C57BL/6 substrains - Kirkpatrick, Stacey L.; Bryant, Camron D. (Frontiers in Behavioral Neuroscience, 2015)
Drug liking versus drug disliking is a subjective motivational measure in humans that assesses the addiction liability of drugs. Variation in this trait is hypothesized to influence vulnerability versus resilience toward substance abuse disorders and likely contains a genetic component. In rodents and humans, conditioned place preference (CPP) / aversion (CPA) is a Pavlovian conditioning paradigm whereby a learned preference for the drug-paired environment is used to infer drug liking whereas a learned avoidance or aversion is used to infer drug disliking. C57BL/6 inbred mouse substrains are nearly genetically identical, yet demonstrate robust differences in addiction-relevant behaviors, including locomotor sensitization to cocaine and consumption of ethanol. Here, we tested the hypothesis that B6 substrains would demonstrate differences in the rewarding properties of the mu opioid receptor agonist oxycodone (5 mg/kg, i.p.) and the aversive properties of the opioid receptor antagonist naloxone (4 mg/kg, i.p.). Both substrains showed similar degrees of oxycodone-induced CPP; however, there was a three-fold enhancement of naloxone-induced CPA in agonist-naïve C57BL/6J relative to C57Bl/6NJ mice. Exploratory factor analysis of CPP and CPA identified unique factors that explain variance in behavioral expression of reward versus aversion. “Conditioned Opioid-Like Behavior” was a reward-based factor whereby drug-free locomotor variables resembling opioid treatment co-varied with the degree of CPP. “Avoidance and Freezing” was an aversion-based factor, whereby the increase in the number of freezing bouts co-varied with the degree of aversion. These results provide new insight into the behavioral architecture of the motivational properties of opioids. Future studies will use quantitative trait locus mapping in B6 substrains to identify novel genetic factors that contribute to the marked strain difference in NAL-CPA.